A new method for sex estimation from maxillary suture length in a Thai population - Apichat Sinthubua (2018)
© 2017. Anatomy & Cell Biology. Sex estimation is one of the crucial procedures in the biological profile identification of human skeletal remains. Knowing sex of unknown case can lead to accurate and appropriate methods for predicting age, stature, ancestry, or even personal identification. Skull is one of the most reliable one among other skeletons and it is usually retained for both archaeological and forensic contexts. Although many morphological features and metric measurements of skull have been studied for sexing, but to the best of our knowledge is no study on maxillary suture length for sex estimation. Therefore, this study aims to develop a new sex estimation method for a Thai population by determining three maxillary suture lengths: anterior, transverse, and posterior maxillary suture, by computerizing amount of pixel obtained from photographs of these sutures. The present study was conducted on 190 Thai bone samples of which 96 were males and 94 were females. Independent t test revealed statistically significant difference (P < 0.01) between males and females in all maxillary suture measurements. Equations derived from prediction model, which required three maxillary suture lengths gave 76.8421% accuracy from the leave-one-out cross validation in estimating sex percentage accuracies in predicting sex from these equations, which were relatively moderate. This study provides a novel and objective sex estimation method for Thais. It suggests that maxillary suture length can be applied for sex estimation. The new computerized technique will contribute basis knowledge and method for sex estimation, especially when only base of skull is available in forensic circumstance.